Study on the performance of different slope inclination of vegetated roof - A. Razak @ Aziz, Nur Syafira (2021)
The vegetated roof is well known for its aesthetic value and is able to save the ecological system. It has the potential to reduce rainwater and air run before it gets to the surface. Rainwater is collected in this system before it is released into the drainage system (drains). The purpose of this study is to diagnose non-vegetative roofing capabilities and vegetation roofs to relieve rainwater flow and to study the abilities of vegetated roofs in hiding rainwater. This study has 4 roofs with 2 vegetated roof and the other 2 roofs is without vegetation. It also has 2 different roof trends (10° and 30°). All the roofs have the same roof size of 600 mm × 600 mm, have a geotextile layer, 80 mm thickness with the same mixture of perlite, vermiculite and peat moss and the plants used for this study are Portulaca Grandiflora. Based on the first findings, vegetated with 30° roof angle collected 4.20 mm while 10° roof angled collected 0.48 mm of rainfall. There is approximately 4 minutes delay for 30° roof before the rainfall being captures from the vegetated roof and 10 minutes delay for 10° roof angle. For light rainfall, the peak of the event recorded was 0.40 mm. Vegetated with 30° roof angled collected 0.05 mm and 10° roof collected 0.045 mm of rainfall which is almost the same value. This shows that 10° and 30° vegetated roof and this shows that vegetated roofs with 30° roof angle did manage to retain certain amount of rainfall but the best roof angle was 10° roof slope because it could retain more rain water compared to 30° roof.